On-edge assembly defect detection in noisy environments using convolutional neural networks - Smit, Janre (Stellenbosch : Stellenbosch University, 2025)
Smit, J. 2025. On-Edge Assembly Defect Detection in Noisy Environments using Convolutional Neural Networks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/07ed5803-7c34-4d1f-add1-9430dd0a134c